2009
DOI: 10.1007/s00383-009-2538-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of N-acetylcysteine on testicular damage in experimental testicular ischemia/reperfusion injury

Abstract: Our results suggest that the early administration of NAC may have a protective effect in the rat experimental testicular T/D models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 23 publications
1
22
2
Order By: Relevance
“…Some investigators have found that unilateral testicular torsion-detorsion causes contralateral testicular damage (Minutoli et al, 2009;Aktaş et al, 2010;Jeong et al, 2010;Yang et al, 2010), whereas other investigators have not (Bozlu et al, 2009;Al-Maghrebi et al, 2010). In our study, although unilateral testicular torsion-detorsion resulted in significant changes in ipsilateral testicular malondialdehyde level, CREM expression, and spermatogenesis, our results did not show any change in the contralateral testes.…”
Section: Discussioncontrasting
confidence: 79%
“…Some investigators have found that unilateral testicular torsion-detorsion causes contralateral testicular damage (Minutoli et al, 2009;Aktaş et al, 2010;Jeong et al, 2010;Yang et al, 2010), whereas other investigators have not (Bozlu et al, 2009;Al-Maghrebi et al, 2010). In our study, although unilateral testicular torsion-detorsion resulted in significant changes in ipsilateral testicular malondialdehyde level, CREM expression, and spermatogenesis, our results did not show any change in the contralateral testes.…”
Section: Discussioncontrasting
confidence: 79%
“…In an experimental study of testis torsion performed on rats, Cay et al (18) determined that tissue MDA levels were significantly higher in both the torsion and torsion-detorsion groups compared with the control group. In a recent study by Aktas x et al (19), MDA levels were significantly higher in the testicular torsion group, but, although MPO levels were higher in the torsion group compared with the control group, the difference was not statistically significant. We determined a significant correlation between histopathologic score and blood and tissue MPO levels.…”
Section: Figurementioning
confidence: 62%
“…They concluded that systemic administration of NAC 30 minutes before torsion or detorsion could increase the level of antioxidant enzymes, as well as reducing the cellular damage manifested by lower levels of MDA and apoptosis compared with the T/D group. More recently, Aktas et al (21) also evaluated the effects of NAC on testicular I/R injury and demonstrated that early administration of NAC may have a protective effect in experimental testicular T/D injury in a rat model.…”
Section: Discussionmentioning
confidence: 96%